Physiological responses of date palm (Phoenix dactylifera) seedlings to acute ozone exposure at high temperature. (November 2018) - Du, Baoguo; Kreuzwieser, Jürgen; Winkler, Jana Barbro; Ghirardo, Andrea; Schnitzler, Jörg-Peter; Ache, Peter; Alfarraj, Saleh; Hedrich, Rainer; White, Philip; Rennenberg, Heinz
Abstract: Vegetation in the Arabian Peninsula is facing high and steadily rising tropospheric ozone pollution. However, little is known about the impacts of elevated ozone on date palms, one of the most important indigenous economic species. To elucidate the physiological responses of date palm to peak levels of acute ozone exposure, seedlings were fumigated with 200 ppb ozone for 8 h. Net CO2 assimilation rate, stomatal conduction, total carbon, its isotope signature and total sugar contents in leaves and roots were not significantly affected by the treatment and visible symptoms of foliar damage were not induced. Ozone exposure did not affect hydrogen peroxide and thiol contents but diminished the activities of glutathione reductase and dehydroascorbate reductase, stimulated the oxidation of ascorbate, and resulted in elevated total ascorbate contents. Total nitrogen, soluble protein and lignin contents remained unchanged upon ozone exposure, but the abundance of low molecular weight nitrogen (LMWN) compounds such as amino acids and nitrate as well as other anions were strongly diminished in leaves and roots. Other nitrogen pools did not benefit from the decline of LMWN, indicating reduced uptake and/or enhanced release of these compounds into the soil as a systemic response to aboveground ozone exposure. Several phenolic compounds, concurrent with fatty acids and stearyl alcohol, accumulated in leaves, but declined in roots, whereas total phenol contents significantly increased in the roots. Together these results indicate that local and systemic changes in both, primary and secondary metabolism contribute to the high tolerance of date palms to short-term acute ozone exposure. Graphical abstract: Image 1 Highlights: Acute ozone exposure only little effected physiological parameters of date palms. Anti-oxidants and turgor balance cooperatively mediate ozone tolerance. Local and systemic changes in metabolites contribute to the ozone tolerance. Root metabolism was impacted by ozone due to altered shoot - root interactions. Abstract : Date palms can grow and develop in an environment with high acute atmospheric ozone levels due to its tolerance to this air pollutant mediated by adaptations of both, primary and secondary metabolisms, as well as whole plant shoot-root interactions.